Efektivitas Rotation Drill Terhadap Kecepatan Reaksi Penjaga Gawang Pada Cabang Olahraga Hoki - Yadi Sunaryadi; Arif Rahman Hakim; Dadan Mulyana (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2022)
The reaction for the hockey goalkeeper is needed to anticipate that the ball does not enter the goal. The purpose of this study was to increase the reaction speed of hockey goalkeepers with the rotation drill method. The rotation drill method is a form of exercise to increase the first speed in multiple directions and react time. The method used is experimental. The subjects in this study were the total 6 person goalkeepers of the Student Activity Unit for hockey. By using a pretest posttest group research design with all samples given an experiment. From the results of research data processing, it was found that the output of the paired sample test of rotation drill exercises on the reaction speed of hockey goalkeepers had a significant effect, it can be concluded that the rotation drill method had a significant effect on increasing the reaction speed of hockey goalkeepers.